Hearing Norton Sound: a community randomised trial protocol to address childhood hearing loss in rural Alaska. Issue 1 (15th January 2019) - Emmett, Susan D; Robler, Samantha Kleindienst; Wang, Nae-Yuh; Labrique, Alain; Gallo, Joseph J; Hofstetter, Philip
Abstract : Introduction: The population in rural Alaska experiences a disproprionately high burden of infection-mediated hearing loss. While the state mandates school hearing screening, many children with hearing loss are not identified or are lost to follow-up before ever receiving treatment. A robust, tribally owned healthcare system exists in Alaska, but children with hearing loss must first be identified and referred for existing infrastructure to be used. This trial will evaluate a new school hearing screening and referral process in rural Alaska, with the goal of improving timely identification and treatment of childhood hearing loss. Methods and analysis: Comparative effectiveness community randomised trial testing digital innovations to improve school hearing screening and referral in 15 communities in the Norton Sound region of northwest Alaska, with data collection from October 2017 to February 2020. All children (K-12) attending school in Bering Strait School District with parental informed consent and child assent will be eligible (target recruitment n=1500). Participating children will undergo both the current school hearing screen and new mobile health (mHealth) screen, with screening test validity evaluated against an audiometric assessment. Communities will be cluster randomised to continue the current primary care referral process or receive telemedicine referral for follow-up diagnosis and treatment. The primary outcome will be time to International Statistical Classification of Diseases, 10th Revision, ear/hearing diagnosis from screening date, measured in days. Secondary outcomes will include: sensitivity and specificity of current school and mHealth screening protocols measured against a benchmark audiometric assessment (air and bone conduction audiometry, tympanometry and digital otoscopy); hearing loss prevalence; hearing-related quality of life; and school performance (AIMSweb). Intention-to-treat analysis will be used. Ethics and dissemination: This study has been approved by the Institutional Review Boards of Alaska Area, Norton Sound and Duke University and is registered on clinicaltrials.gov. Results will be distributed with equal emphasis on scientific and community dissemination. Trial registration number: NCT03309553 ; Pre-results.